THE COOPERATION BETWEEN COMPANIES AND UNIVERSITIES AND ITS REFLECTIONS IN THE INFORMATION SOCIETY (Revista Justiça do Direito, 2015)
It will be discussed in this article, as an introductory character, the cooperation between companies and universities as an instrument for the promotion of technological progress, which is an essential element for the economic and social development of a nation. Thus, there will be discussed aspects related to open innovation, protection of intangible assets arising from the cooperation, technology transfer agreements and licensing of intellectual property rights as a means of integration between Brazilian companies and universities with foreign companies and the consequent increase in international relationships as well as economic and technological development of the involved actors. Brazil occupies a prominent position in the international trade; therefore it denotes the relevance in addressing the integration between companies and universities that are outstanding in creating new technologies and its impact on the information society.Key-Words: Companies; Cooperation; Intellectual Property; Technology transfer agreements; Universities.